1989
DOI: 10.1159/000480959
|View full text |Cite
|
Sign up to set email alerts
|

Effect of in utero Cocaine Exposure on Startle and Its Modification

Abstract: The effect of prenatal cocaine on acoustic sensorineural reactivity was assessed using reflex modification procedures in infants born to mothers with cocaine abuse (C-exposed). Reflex modification was tested using a controlled eyeblink-eliciting tap to the glabella presented either alone or with a 90-dB SPL tone. The results from 19 C-exposed infants were compared to 19 healthy matched drug-free infants. ANOVA comparison of the two groups showed C-exposed infants were more reactive in general, as indicated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Gap-PPI, assessed using the eyeblink startle paradigm, has been used to assess tinnitus deficits in humans, also providing critical information regarding the underlying neural circuitry (Fournier and Hebert 2013). The eyeblink startle paradigm has also been used to assess the effects of prenatal cocaine exposure (Anday et al 1989) and chronic cocaine use (Corcoran et al 2011; Efferen et al 2000). Most notably, alterations in temporal processing have been observed in HIV-1 seropositive individuals with HAND using the eyeblink startle paradigm (Minassian et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Gap-PPI, assessed using the eyeblink startle paradigm, has been used to assess tinnitus deficits in humans, also providing critical information regarding the underlying neural circuitry (Fournier and Hebert 2013). The eyeblink startle paradigm has also been used to assess the effects of prenatal cocaine exposure (Anday et al 1989) and chronic cocaine use (Corcoran et al 2011; Efferen et al 2000). Most notably, alterations in temporal processing have been observed in HIV-1 seropositive individuals with HAND using the eyeblink startle paradigm (Minassian et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The variability in results is not surprising given that different species, drug dosages, routes of administration, and postnatal ages at testing have been employed. For example, the amplitude of the reflexive eyeblink elicited by glabellar tap is increased in human infants exposed to cocaine in utero , 44 whereas neither tail‐flick latencies of weanling rats nor footshock sensitivity of 12‐day‐old rat pups are affected by prenatal exposure to cocaine. 45,46 Mixed results have also been reported for adult animals.…”
Section: Long‐term Sensorimotor Effects Of Prenatal Exposure To Cocainementioning
confidence: 99%
“…Rabbits typically show augmentation of NM reflex amplitude and reduction of NM reflex latency when that reflex is preceded by a moderate intensity tone at intervals in the range of 200–800 ms. 61,63–66 There have been mixed reports of reflex modification effects in rats and human infants following prenatal exposure to cocaine. 44,49–51…”
Section: Long‐term Sensorimotor Effects Of Prenatal Exposure To Cocainementioning
confidence: 99%
“…Infants with PCE were overreactive to a variety of stimuli, which, in part, may indicate that children with PCE may habituate more slowly to stimuli than do infants with NCE (Potter, Zelazo, Stack, & Papageorgiou, 2000). Additionally, researchers have found that infants with PCE startled more with auditory stimuli than did children with NCE, with cocaine exposure appearing to have a direct effect on sensorineural processing (Anday, Cohen, Kelley, & Leitner, 1989). Auditory evoked potentials from the brainstem and the cortex suggested some abnormalities in central auditory processing during the newborn period in children with PCE (Cone-Wesson, 2005; Tan-Laxa, Sison-Switala, Rintelman, & Ostrea, 2004).…”
Section: Review Of Language Findings By Age At Assessmentmentioning
confidence: 99%